Effect of GA3, IAA and their mixtures on the formation and development of cell systems in the vegetative and generative thallus of Chara vulgaris L. - Maria Kwiatkowska; Aleksandra Gosek; Mirosław Godlewski (Acta Societatis Botanicorum Poloniae, 2014)
In concentrations ranging from 10-7 to 10-5 M IAA strongly stimulates the growth of the main axis and pleuridia internodal cells, while it does not affect the number of lateral branches and generative organs. In the higher concentrations it reduces the number of spermatozoids in the antheridium. In the same concentration range, GA3, inhibits the growth of the main axis and pleuridia internodal cells, does not affect the number of lateral branches, increases the number of antheridia and increases the number of forming spermatozoids. Incubation in mixture of both regulators has shown that: a) IAA eliminates the inhibitory effect of GA3 on the growth of internodal cells of the main axis and its stimulatory action is slightly weakened by GA3, b) IAA in a concentration of 10-5 M along with a low concentration of GA3, (10-7) increases the number of main axis lateral branches. The conclusion is drawn that the growth of the vegetative part of the thallus is more intense when auxin predominates, but generative development requires a high level of gibberellin.